Turning point - Chase, Paula (Greenwillow Books, an Imprint of HarperCollinsPublishers, 2020)
Middle schoolers and best friends Rasheeda Tate and Monique Jenkins are good girls. For Sheeda, that means keeping her friends close and following Auntie D's every rule--especially when it comes to church and boys. But when her secret relationship with Mo's older brother Lennie goes from texting to something more, the line between good and bad decisions gets blurry. For Mo, that means learning to go with the flow at the prestigious and mostly White ballet program she's been accepted to on scholarship. But when the not-so-invisible racial barriers holding her back make her question what she's willing to change to succeed, the difference between strong and weak is hard to see. When being yourself isn't good enough, where do you turn? Sheeda and Mo are about to find out.